2020
DOI: 10.3390/f11121263
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Forest Use Strategies for Cash Income between Households Living outside and inside Selectively Logged Production Forests in Myanmar

Abstract: In many tropical regions, rural households often depend on forests for cash income, but there is still little knowledge on how forest use strategies differ among people living in different locations. This study aimed to detect differences in forest use strategies and forest cash income dependency between households living outside and inside selectively logged production forests, known as Reserved Forests (RFs), in Bago Township, Myanmar. A questionnaire survey was conducted with 146 and 48 households living ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Thus, it may be an option to provide a legal right for local households to use bamboo resources sustainably, coupled with a strategy for restoring bamboo-dominated forests. In contrast, most of the encroachers in RFs were illegally engaged in charcoal making [27] and this present study has indicated that this illegal activity is a major factor of forest degradation. Because there is still an increasing demand for charcoal in rural areas in Myanmar [36], the establishment of a sustainable charcoal production system should be targeted through community forestry programs.…”
Section: Stand Structure After Legal and Illegal Logging And Manageme...mentioning
confidence: 49%
See 3 more Smart Citations
“…Thus, it may be an option to provide a legal right for local households to use bamboo resources sustainably, coupled with a strategy for restoring bamboo-dominated forests. In contrast, most of the encroachers in RFs were illegally engaged in charcoal making [27] and this present study has indicated that this illegal activity is a major factor of forest degradation. Because there is still an increasing demand for charcoal in rural areas in Myanmar [36], the establishment of a sustainable charcoal production system should be targeted through community forestry programs.…”
Section: Stand Structure After Legal and Illegal Logging And Manageme...mentioning
confidence: 49%
“…This is in contrast to Win et al [20] and Khai et al [17,21] who indicated that more illegal logging occurred for high-quality timber species such as teak and pyinkado. Our study plots were within compartments where people had settled illegally, and Saung et al [27] indicated that such encroachers mostly engaged in charcoal making to generate income (see the photos 3 and 6 in the Supplementary Material S1). Our GLM result on the preference for charcoal species for illegal logging is compatible with the survey results on charcoal making as a livelihood strategy [27].…”
Section: Legal and Illegal Loggingmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost 95 % of rural population is entirely dependent upon the forest products for basic needs while only 6 % of total cash income is contributed by the forest products in the north-west region of Myanmar (Hlaing et al 2017). Likely, the contribution of NTFPs to household income varies in different regions such as 25 % to 36 % of total household income derived from NTFPs in eastern and western Bago Yoma, 38 % in the central dry zone, 55 % in Chin State, and 53 % in the eastern mountain range which is called Shan Yoma; meaning that NTFPs also provide an alternative income source for landless people during the off-farm season and when there is a shortfall of agricultural products (Oo et al 2012, Aung et al 2015, Moe and Liu 2016, Htun et al 2017, Soe and Yeo-Chaung 2019, Saung et al 2020. At the national level, the share of national gross domestic products (GDP) from forestry sector was 0.6 % in the fiscal year of (2005 2006) which declines to 0.2 % in 2015 2016 and 0.08 % in 2019 (CSO 2020).…”
Section: Introductionmentioning
confidence: 99%